Reading as the Angels Read : Speculation and Politics in Dante's 'Banquet' - Ardizzone, Maria Luisa (Book collections on Project MUSE., 2016)
"An uncompleted manuscript that combines lyric poetry and prose commentary, the Banquet (or Convivio) is one of Dante Alighieri's most important and least understood philosophical texts. As Maria Luisa Ardizzone shows, its language and logic are deeply connected to medieval culture and the philosophical debates of the thirteenth and early fourteenth centuries. In Reading as the Angels Read, Ardizzone reconstructs the cultural and socio-political background that provided the motivation for the Banquet and offers a bold new reading of this ambitious work. Drawing on a deep knowledge of Dante's engagement with biblical, Augustinian, Neoplatonic, and Aristotelian philosophy, she suggests that the Banquet is not an encyclopedia of learning as many have claimed, but Dante's attempt to articulate a theory of human happiness in which perfect knowledge is the natural basis for a well-organized political community."--